Avaliação tribológica dos polímeros NBR, PTFE e PTFE gravitado em contato com aço AISI 52100 - Santana, Janaina Silva de (2009)
Low cost seals are made of NBR, Nitrile Butadiene Rubber, a family of unsaturated copolymers that is higher resistant to oils the more content of nitrile have in its composition, although lower its flexibility. In Petroleum Engineering, NBR seal wear can cause fluid leakage and environmental damages, promoting an increasing demand for academic knowledge about polymeric materials candidate to seals submitted to sliding contacts to metal surfaces. This investigation aimed to evaluate tribological responses of a commercial NBR, hardness 73 ± 5 Sh A, polytetrafluoroethylene (PTFE), hardness 60 ± 4 HRE and PTFE with graphite, 68 ± 6 HRE. The testings were performed on a sliding tribometer conceived to explore the tribological performance of stationary polymer plane coupons submitted to rotational cylinder contact surface of steel AISI 52100, 20 ± 1 HRC Hardness, under dry and lubricated (oil SAE 15W40) conditions. After screening testings, the normal load, relative velocity and sliding distance were 3.15 N, 0.8 m/s and 3.2 km, respectively. The temperatures were collected over distances of 3.0±0.5 mm and 750±50 mm far from the contact to evaluate the heating in this referential zone due to contact sliding friction by two thermocouples K type. The polymers were characterized through Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC) and Dynamic Mechanical Analysis (DMA). The wear mechanisms of the polymer surfaces were analyzed by Scanning Electron Microscopy (SEM) and EDS (Energy-Dispersive X-ray Spectroscopy). NBR referred to the higher values of heating, suggesting higher sliding friction. PTFE and PTFE with graphite showed lower heating, attributed to the delamination mechanism